2006
DOI: 10.1097/01.tp.0000205182.96861.3a
|View full text |Cite
|
Sign up to set email alerts
|

Access to Kidney Transplantation in France of Non-French Patients and French Patients Living in Overseas Territories

Abstract: Median waiting time differed significantly between groups, from 13.8 months for mainland French patients to 39.5 months for sub-Saharan African patients. After adjustment for other factors significantly linked to waiting time, French residents of FOT (RR=0.83; P<0.001) and patients from sub-Saharan Africa (RR=0.75; P<0.0001) were found to wait significantly longer than other patients. HLA matching level, particularly HLA-A and HLA-B, was worse for African patients. After adjustment for the transplant team, col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…We also found that patients with Swedish citizenship had higher chance of access to kidney transplantation compared to non-Swedish patients, which was consistent with a French study [25]. The suggested reason may be that patients of non-Swedish were less likely to have an adequate Human Leukocyte Antigen (HLA)—and blood group-matched kidney than patients of European origin [25]. Socioeconomic and culture factors may also limit access to kidney transplantation [39], however Sweden provides healthcare coverage for other citizenship similar to Swedish citizenship so financial obstacles to kidney transplantation should be much smaller than in other countries.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We also found that patients with Swedish citizenship had higher chance of access to kidney transplantation compared to non-Swedish patients, which was consistent with a French study [25]. The suggested reason may be that patients of non-Swedish were less likely to have an adequate Human Leukocyte Antigen (HLA)—and blood group-matched kidney than patients of European origin [25]. Socioeconomic and culture factors may also limit access to kidney transplantation [39], however Sweden provides healthcare coverage for other citizenship similar to Swedish citizenship so financial obstacles to kidney transplantation should be much smaller than in other countries.…”
Section: Discussionsupporting
confidence: 92%
“…The potential mechanism may be spousal kidney donation, more developed social networking, and more qualified for kidney transplantation duo to less depression [36] and positive health behaviors in terms of alcohol and drug abuse [37,38]. We also found that patients with Swedish citizenship had higher chance of access to kidney transplantation compared to non-Swedish patients, which was consistent with a French study [25]. The suggested reason may be that patients of non-Swedish were less likely to have an adequate Human Leukocyte Antigen (HLA)—and blood group-matched kidney than patients of European origin [25].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…An Israeli study showed similar results 26. There are no Canadian data on this issue, and the situation might be different from that in the USA, of Canada's universal health insurance; for example, in France, where there is also universal health insurance, the proportion of FN patients waitlisted for an organ transplant increased between 1996 and 2008 13 16…”
Section: Arguments Regarding Transplantations For Foreign Nationalsmentioning
confidence: 92%
“…In general, nations with greater transplantation resources may permit limited access to LTRRT for non-nationals, while those with fewer resources tend to exclude such patients from their programmes (Table 2). [14,17,25,26,28,[29][30][31][32][33][34][35]…”
Section: Access To Dialysis For Non-nationals: International Policymentioning
confidence: 99%